Additions to the knowledge of solitary wasps (Hymenoptera: Vespidae: Eumeninae), with description of eight new species - Selis, Marco (Zootaxa, 2018)
New additions to the knowledge of the subfamily Eumeninae are provided. Eight new species of Eumeninae are described: Antepipona gibbosissima Selis, sp. nov. (Namibia: Warmbad); Antepipona tricolorata Selis, sp. nov. (India: Sikkim); Ectopioglossa luzonica Selis, sp. nov. (Philippines: Luzon); Lissodynerus unicus Selis, sp. nov. (India: Sikkim); Pararrhynchium aurigaster Selis, sp. nov. (Malaysia: Johor); Symmorphus (Symmorphus) incisus Selis, sp. nov. (India: Sikkim); Symmorphus (Symmorphus) palawanensis Selis, sp. nov. (Philippines: Palawan); Zethus (Zethus) intermedius Selis, sp. nov. (Burkina Faso). The male of Synagris (Paragris) biplagiata Gusenleitner, 2005 is described. New distributional data for other species are provided.